A terceira margem da performance: um estudo do ato-narrativo em Três contos de Guimarães Rosa - Barros, Wellington Rodrigues (2017)
This dissertation studies the relation between the concept of narrative and performance based on the phenomenon of telling stories applied in three short stories of Guimarães Rosa: 'The Heppiness Margin', 'The Mirror' e 'The Third Margin of the River', form the book 'First Stories' (1988). Methodologically this work consists in a corpus referring in the performance narrative of the own author with two more performers, and with the audiovisual datas in order to reflect in the analyze and in the materialization of the narrative act.